Memories from the Margins: Stories and Images of Urban Homelessness - Cynthia J. Miller (Linguaculture, 2012)
Among any city’s most wounded bodies and minds are the homeless - individuals who live on the streets, without any formal claim to place. For many of these individuals, the vessels of historical memory are not museums, or classrooms, or library archives, but parks, alleyways, and subway stations. As the numbers of homeless individuals increase dramatically each year, their social, physical, and psychological trauma increasingly characterizes urban life, even as their experiences fall to the margins of the city’s history and future. In response, this paper explores the merging of homeless histories with public history, through two interlocking projects carried out in Boston, Massachusetts - “Histories and Homelessness,” a community-based life-writing project, and “Images from the Streets,” a disposable-camera photography project - outreach and education projects, in which all participants are among the unsheltered homeless who spend their nights on heating grates, under highways, and in ATM kiosks. Together, these projects begin to map and make visible the landscape and memories of homelessness, as they are written and photographed by its inhabitants, and firmly situate these histories within the wider community. Recovering the personal and interpretive histories of homeless individuals, so intimately tied to “place,” creates a powerful strategy for expanding the history of the community to include voices and visions often excluded or left at the margins.